Synthesis A.nd Study The Biological Activity of Some Schiff-Bases Derived F,rom 2- Aminothiazole or 2-Aminobenzothiazole and Vanillin Derivatives - Afi, E. T.; Tomma, J. H.; Mubbr k, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Two series of 1,n-alkylene glycol di [4N(T-thiazolylazoÂ nrethinyl)2-metho y] phenyl ether and I ,n-alkylene glycol di[4N(r-benzo-thiazolylazomethinyl)2-methoxy]phenyl ether were synthesize-d via rea tions 2-aminothiazole and 2-aminobenzothiazole with dialdehyde â€¢ (which are synthesized from .reaction vanil.lin with l ,n-dibromo or ehloro. alkane in the basic me’dia ) . The new compounds characterized by elemental analysis (of some of theme) , physical and spectral data .All the schiff-bases have been screened for their antifungal and antibacterial activity against Aspergillus niger ,. Escherichi coli (0-) and Staphylococcus aureus . (G+) . AlJ compounds were found to be active antibacterial and antifungal (except [III] 12 was not show any antifungal activity).